Insights into effect of first-step austempering temperature on the microstructure and properties of austempered ductile iron. (20th August 2021) - Zhang, Yu; Guo, Erjun; Wang, Liping; Zhao, Sicong; Liu, Xiaoyu; Yi, Pengyue; Li, Yan; Feng, Yicheng; Song, Meihui
Abstract: Austempered ductile iron (ADI) is a revolutionary material with high strength and hardness combined with excellent ductility and toughness. The discovery of a two-step austempering process has resulted in superior combination of all the mechanical properties. Therefore, ADI has many different applications in varying fields. One notable application of ADI is in transmission components for new energy vehicles. As the automotive continues to develop, ADI transmission components with higher damping properties are required, because the damping properties of ADI affect the vibration and noise of the transmission system. However, the mechanism behind the damping of ADI, as well as a full characterisation of the damping properties, has not been thoroughly investigated in the literature. Therefore, it is necessary to reveal the influencing factors and mechanism of the damping properties of ADI. In this paper, the effect of first-step austempering temperature on the microstructure, mechanical properties, and damping properties of ADI was investigated. The results revealed that the tensile strength, yield strength, and elongation of ADI all initially increased, until reaching a global maximum value (1320 MPa, 1230 MPa, and 13.2%, respectively) when the first-step austempering temperature was 280 °C, followed by a decrease in value. Interestingly, the impact energy of ADI initially decreased before reaching a global minimum and then increasing to a maximum value of 93.5 J, when the first-step austempering temperature reached 320 °C. With increasing strain amplitude, the internal friction values (Q −1 ) of ADI treated with different first-step austempering temperatures all increased gradually, and the Q −1 values of ADI with first-step austempering temperatures of 240 and 260 °C were higher than those of other samples. Moreover, the damping properties of ADI varied with frequency with obvious S-K peaks and Ge peaks.